Analysis of molecular mechanisms of 5-fluorouracil-induced steatosis and inflammation in vitro and in mice - Sommer, Judith; Mahli, Abdo; Freese, Kim; Schiergens, Tobias S.; Kuecuekoktay, Fulya Suzan; Teufel, Andreas; Thasler, Wolfgang E.; Mueller, Martina; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Oncotarget, 2017)
Chemotherapy-associated steatohepatitis is attracting increasing attention because it heralds an increased risk of morbidity and mortality in patients undergoing surgery because of liver metastases. The aim of this study was to develop in vitro and in vivo models to analyze the pathogenesis of 5-fluorouracil (5-FU)-induced steatohepatitis.Therefore, primary human hepatocytes and HepG2 hepatoma cells were incubated with 5-FU at non-toxic concentrations up to 24 h. Furthermore, hepatic tissue of C57BL/6N mice was analyzed 24 h after application of a single 5-FU dose (200 mg/kg body weight). In vitro, incubation with 5-FU induced a significant increase of hepatocellular triglyceride levels. This was paralleled by an impairment of mitochondrial function and a dose- and time-dependently increased expression of fatty acid acyl-CoA oxidase 1 (ACOX1), which catalyzes the initial step for peroxisomal ?-oxidation. The latter is known to generate reactive oxygen species, and consequently, expression of the antioxidant enzyme heme oxygenase 1 (HMOX1) was significantly upregulated in 5-FU-treated cells, indicative for oxidative stress. Furthermore, 5-FU significantly induced c-Jun N-terminal kinase (JNK) activation and the expression of pro-inflammatory genes IL-8 and ICAM-1. Also in vivo, 5-FU significantly induced hepatic ACOX1 and HMOX1 expression as well as JNK-activation, pro-inflammatory gene expression and immune cell infiltration. In summary, we identified molecular mechanisms by which 5-FU induces hepatocellular lipid accumulation and inflammation. Our newly developed models can be used to gain further insight into the pathogenesis of 5-FU-induced steatohepatitis and to develop therapeutic strategies to inhibit its development and progression.
EVALuna2:4753

Bone Morphogenetic Protein-8B Expression is Induced in Steatotic Hepatocytes and Promotes Hepatic Steatosis and Inflammation In Vitro - Mahli, Abdo; Seitz, Tatjana; Beckroege, Tobias; Freese, Kim; Thasler, Wolfgang Erwin; Benkert, Matthias; Dietrich, Peter; Weiskirchen, Ralf; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Cells, 2019)
Non-alcoholic fatty liver disease (NAFLD) is considered to be the hepatic manifestation of the metabolic syndrome. The bone morphogenetic protein-8B (BMP8B) has been shown to be expressed in brown adipose tissues and the hypothalamus and to affect thermogenesis and susceptibility to diet-induced obesity. Here, we aimed to analyze BMP8B expression in NAFLD and to gain insight into BMP8B effects on pathophysiological steps of NAFLD progression. BMP8B mRNA and protein expression were dose-dependently induced in primary human hepatocytes in vitro upon incubation with fatty acids. Furthermore, hepatic BMP8B expression was significantly increased in a murine NAFLD model and in NAFLD patients compared with controls. Incubation with recombinant BMP8B further enhanced the fatty acid-induced cellular lipid accumulation as well as NFB activation and pro-inflammatory gene expression in hepatocytes, while siRNA-mediated BMP8B depletion ameliorated these fatty acid-induced effects. Analysis of the expression of key factors of hepatocellular lipid transport and metabolisms indicated that BMP8B effects on fatty acid uptake as well as de novo lipogenesis contributed to hepatocellular accumulation of fatty acids leading to increased storage in the form of triglycerides and enhanced combustion by beta oxidation. In conclusion, our data indicate that BMP8B enhances different pathophysiological steps of NAFLD progression and suggest BMP8B as a promising prognostic marker and therapeutic target for NAFLD and, potentially, also for other chronic liver diseases.
CRIS-Team WoS Importer:2019-06-28

Combined effects of PLK1 and RAS in hepatocellular carcinoma reveal rigosertib as promising novel therapeutic "dual-hit" option - Dietrich, Peter; Freese, Kim; Mahli, Abdo; Thasler, Wolfgang Erwin; Hellerbrand, Claus; Boßerhoff, Anja Katrin (Oncotarget, 2018)
Inhibition of RAS-RAF-ERK-signaling is a major mechanism mediated by the multi-kinase inhibitors sorafenib and regorafenib, the only effective therapeutic approaches for advanced hepatocellular carcinoma (HCC). This underlines the importance of RAS-RAF-ERK-signaling in HCC. Most RAS isoforms were not yet described to play crucial roles in HCC. However, several studies indicate that the HRAS isoform can function as potent oncogene in HCC, but pharmacologic RAS inhibition has not yet been investigated. Moreover, the cell cycle promoting polo-like kinase 1 (PLK1) is an increasingly recognized therapeutic target in HCC that can be activated by RAS-RAF-signaling. A recently developed small molecule inhibitor, ON-01910 ("rigosertib", RGS), was shown to interfere with both RAS- and PLK1-signaling. The aim of this study was to analyze the effects of RGS in HCC and to assess PLK1 and HRAS expression in HCC. RGS treatment reduced cell proliferation and induced cell cycle arrest in human HCC cell lines in vitro. Moreover, RGS strongly inhibited both ERK- and AKT-activation in HCC cells, indicating disruption of RAS-signaling. Analysis of HCC patient data showed that PLK1 and HRAS expression levels are upregulated during HCC development and in advanced HCC, respectively. High expression levels of PLK1 significantly correlated with poor patient survival. Moreover, high expression of both PLK1 and HRAS revealed combined effects on patient outcome. This underscores the importance of these genes and associated pathways in HCC. We newly demonstrate the therapeutic potential of RGS in HCC by inhibition of both PLK1 activation and major RAS-pathways, revealing a novel therapeutic "dual-hit" approach for HCC.
EVALuna2:34067

Development of an in vitro model to study hepatitis C virus effects on hepatocellular lipotoxicity and lipid metabolism - Koletzko, Leandra; Mahli, Abdo; Hellerbrand, Claus (Pathology Research and Practice, 2018)
Hepatic steatosis is common in patients infected with hepatitis C virus (HCV). Particularly in patients infected with non-genotype 3 HCV, hepatic steatosis is closely related to factors of the metabolic syndrome such as hyperlipidemia. However, the molecular mechanisms involved in this "metabolic" steatosis in non-3 genotype HCV infections are not well understood. Here, we aimed to develop an in vitro model to study the effect of genotype 1 HCV infection on hepatic lipotoxicity and lipid metabolism. Cellular lipid accumulation was induced in Huh-7 hepatoma cells transfected with HCV genotype 1b replicon (HCV+) by incubation with increasing doses of palmitic acid (C16:0) or oleic acid (C18:1 n-9) complexed to albumin mimicking hyperlipidemic conditions. Mock transfected hepatoma cells (HCV-) were used as controls. Incubation with oleic acid concentrations as high as 0.5 mM did not induce toxic effects in HCV+ or HCV- cells. In contrast, incubation with palmitic acid caused dose-dependently cytotoxic effects which were more pronounced in HCV+ compared to HCV- cells. Further analysis with subtoxic palmitic and oleic acid concentrations revealed a higher uptake of fatty acids and intracellular triglyceride accumulation in HCV+ compared to HCV- cells. Carnitine palmitoyltransferase I (CPT1) expression, indicative of mitochondrial beta-oxidation, was markedly stimulated by lipid exposure in HCV+ but not in HCV- cells. Furthermore, heme oxygenase 1 (HMOX1) expression levels increased in FA stimulated cells, and this increase was significantly higher in HCV+ compared to HCV- cells. In contrast, expression of the key enzymes of hepatic de novo lipogenesis fatty acid synthase (FASN) and stearoyl-CoA desaturase (SCD-1) was significantly reduced upon oleate exposure in HCV- but not in HCV+ cells. In summary, our newly developed cell culture model revealed effects of HCV genotype 1b infection on metabolic susceptibility to lipid accumulation and toxicity particularly to saturated lipids. These results may indicate that HCV (genotype 1b) infected individuals with hyperlipidemia may benefit from dietary or pharmacological intervention.
EVALuna2:35809

Establishment of a p-nitrophenol oxidation-based assay for the analysis of CYP2E1 activity in intact hepatocytes in vitro - Mahli, Abdo; Thasler, Wolfgang Erwin; Hellerbrand, Claus (Toxicology Mechanisms and Methods, 2019)
CYP2E1 is a mammalian cytochrome P450 enzyme, which oxidizes a structurally diverse class of endogenous and exogenous (xenobiotic) compounds. Best studied is the role of CYP2E1 in phase I metabolism of xenobiotics including alcohol. CYP2E1 metabolizes ethanol and is active in generating reactive oxygen species (ROS) and subsequent oxidative stress in the hepatic tissues. Several studies have shown and discussed the importance of CYP2E1 in the hepatotoxic actions of alcohol. However, the vast majority assessed the CYP2E1 activity only in isolated microsomes. Here, we aimed to develop and optimize a fast and easy method to assess alcohol-induced CYP2E1 activity in hepatocytes in vitro applying oxidation of para-nitrophenol to para-nitrocatechol as specific substrate probe. Using hepatoma cells with and without stable CYP2E1 expression and primary human hepatocytes, we established specific methodology to assess CYP2E1 catalytic activity and its induction by ethanol in a small number of cells and in a very short time.
CRIS-Team WoS Importer:2019-04-12

Hepatic steatosis potentiates irinotecan-induced hepatocellular injury via dysregulation of irinotecan-metabolizing enzymes - Mahli, Abdo; Koch, Angelika; Thasler, W.; Hellerbrand, Claus (JOURNAL OF HEPATOLOGY, 2018)
CRIS-Team WoS Importer:2019-03-26

Hop-derived Humulinones Reveal Protective Effects in in vitro Models of Hepatic Steatosis, Inflammation and Fibrosis. - Mahli, Abdo; Thasler, Wolfgang E.; Biendl, Martin; Hellerbrand, Claus (Planta Medica, 2023)
Nonalcoholic fatty liver disease (NAFLD) is emerging as leading cause of liver disease worldwide. Specific pharmacologic therapy for NAFLD is a major unmet medical need. Recently, iso-alpha acids, hop-derived bitter compounds in beer, have been shown to beneficially affect NAFLD pathology. Humulinones are further hop derived bitter acids particularly found in modern styles of beer. So far, biological effects of humulinones have been unknown. Here, we investigated the effect of humulinones in in vitro models for hepatic steatosis, inflammation and fibrosis. Humulinones dose-dependently inhibited fatty acid induced lipid accumulation in primary human hepatocytes. Humulinones reduced the expression of fatty acid uptake transporter CD36 and key enzymes of (de novo) lipid synthesis. Conversely, humulinones increased the expression of FABP1, CPT1 and ACOX1, indicative for increased lipid combustion. Furthermore, humulinones ameliorated steatosis induced pro-inflammatory gene expression. Furthermore, humulinones significantly reduced the expression of pro-inflammatory and pro-fibrogenic factors in control as well as lipopolysaccharide treated activated hepatic stellate cells, which play a key role in hepatic fibrosis. In conclusion, humulinones beneficially affect different pathophysiological steps of NAFLD. Our data suggest humulinones as promising therapeutic agents for the prevention and treatment of NAFLD.
EVALuna2:536972

Iso-alpha acids from hops (Humulus lupulus) inhibit hepatic steatosis, inflammation, and fibrosis - Mahli, Abdo; Koch, Andreas; Fresse, Kim; Schiergens, Tobias; Thasler, Wolfgang Erwin; Schoenberger, Christina; Bergheim, Ina; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Laboratory Investigation, 2018)
Non-alcoholic fatty liver disease (NAFLD) is considered to be the hepatic manifestation of the metabolic syndrome. Iso-alpha acids (IAAs), hop-derived bitter compounds in beer, have been shown to beneficially affect different components of the metabolic syndrome such as insulin resistance and dyslipidemia. However, IAAs have not yet been studied in the context of chronic liver disease. Here we analyzed the effect of IAA on the pathogenesis of NAFLD. Once, we applied IAA to mice in combination with a NAFLD-inducing Western-type diet (WTD), and observed that IAA significantly inhibited WTD-induced body weight gain, glucose intolerance, and hepatic steatosis. Fitting to this, IAA dose-dependently inhibited cellular lipid accumulation in primary human hepatocytes (PHH) in vitro. Reduced expression of PPAR-gamma and key enzymes of lipid synthesis as well as increased expression of PPAR-alpha, indicative for increased lipid combustion, were identified as underlying mechanisms of reduced hepatocellular steatosis in vitro and in vivo. Analysis of hepatic HMOX1 expression indicated reduced oxidative stress in IAA-treated mice, which was paralleled by reduced activation of the JNK pathway and pro-inflammatory gene expression and immune cell infiltration. Furthermore, IAA reduced hepatic stellate cell (HSC) activation and pro-fibrogenic gene expression. Similarly, IAA also dose-dependently reduced oxidative stress and JNK activation in steatotic PHH, inhibited HSC activation, and reduced proliferation and pro-fibrogenic gene expression in already activated HSC in vitro. In conclusion, IAAs inhibit different pathophysiological steps of disease progression in NAFLD. Together with previous studies, which demonstrated the safety of even long-term application of IAA in humans, our data suggest IAA as promising therapeutic agent for the prevention and treatment of (non)alcoholic (fatty) liver disease.
EVALuna2:35807

STEATOSIS: A LUBRICANT FOR THE DEVELOPMENT AND PROGRESSION OF ALCOHOLIC LIVER DISEASE - Mahli, Abdo; Sommer, Judith; Koch, A.; Hellerbrand, Claus (ALCOHOLISM-CLINICAL AND EXPERIMENTAL RESEARCH, 2021)
CRIS-Team WoS Importer:2021-07-02

Therapeutic Application of Micellar Solubilized Xanthohumol in a Western-Type Diet-Induced Mouse Model of Obesity, Diabetes and Non-Alcoholic Fatty Liver Disease - Mahli, Abdo; Seitz, Tatjana; Freese, Kim; Frank, Jan; Weiskirchen, Ralf; Abdel-Tawab, Mona; Behnam, Dariush; Hellerbrand, Claus (Cells, 2019)
Xanthohumol (XN), a prenylated chalcone from hops, has been reported to exhibit a variety of health-beneficial effects. However, poor bioavailability may limit its application in the prevention and therapy of diseases. The objective of this study was to determine whether a micellar solubilization of xanthohumol could enhance the bioavailability and biological efficacy of xanthohumol in a Western-type diet (WTD) induced model of obesity, diabetes and non-alcoholic fatty liver disease (NAFLD). After 3 weeks feeding with WTD, XN was additionally applied per oral gavage as micellar solubilizate (s-XN) or native extract (n-XN) at a daily dose of 2.5 mg/kg body weight for a further 8 weeks. Control mice received vehicle only in addition to the WTD. WTD-induced body weight-gain and glucose intolerance were significantly inhibited by s-XN application. Furthermore, WTD-induced hepatic steatosis, pro-inflammatory gene expression (MCP-1 and CXCL1) and immune cell infiltration as well as activation of hepatic stellate cells (HSC) and expression of collagen alpha I were significantly reduced in the livers of s-XN-treated mice compared to WTD controls. In contrast, application of n-XN had no or only slight effects on the WTD-induced pathological effects. In line with this, plasma XN concentration ranged between 100-330 nmol/L in the s-XN group while XN was not detectable in the serum samples of n-XN-treated mice. In conclusion, micellar solubilization enhanced the bioavailability and beneficial effects of xanthohumol on different components of the metabolic syndrome including all pathological steps of NAFLD. Notably, this was achieved in a dose more than 10-fold lower than effective beneficial doses of native xanthohumol reported in previous in vivo studies.
CRIS-Team WoS Importer:2019-06-18

Xanthohumol ameliorates acute alcohol-induced liver injury - Mahli, Abdo; Koch, A.; Seitz, Tatjana; Bergheim, I.; Hellerbrand, Claus (ALCOHOLISM-CLINICAL AND EXPERIMENTAL RESEARCH, 2022)
CRIS-Team WoS Importer:2022-09-23

Xanthohumol, a prenylated chalcone derived from hops, inhibits growth and metastasis of melanoma cells - Seitz, Tatjana; Hackl, Christina; Freese, Kim; Dietrich, Peter; Mahli, Abdo; Thasler, Reinhard Manfred; Thasler, Wolfgang Erwin; Lang, Sven Arke; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Cancers, 2021)
Melanoma is one of the most aggressive and lethal cancers worldwide. Despite recent progress in melanoma therapy, the prognosis for metastasized melanoma continues to be poor. Xan-thohumol (XN), a prenylated chalcone derived from hop cones, is known to possess a broad spectrum of chemopreventive and anticancer activities. However, few studies have analyzed functional XN effects on melanoma cells and there have been no previous in vivo studies of its effects on metastasis. The aim of this study was to investigate the impact of XN on the tumorigenic and liver metastatic activity of melanoma cells. XN exhibited dose-dependent cytotoxic effects on human melanoma cell lines (Mel Ju; Mel Im) in vitro. Functional analysis in the subtoxic dose-range revealed that XN dose-dependently inhibited proliferation, colony formation, and migratory activity of melanoma cells. Subtoxic XN doses also induced markers of endoplasmic reticulum stress but inhibited the phosphorylation of the protumorigenic c-Jun N-terminal kinases (JNK). Furthermore, XN effects on hepatic metastasis were analyzed in a syngeneic murine model (splenic injection of murine B16 melanoma cells in C57/BL6 mice). Here, XN significantly reduced the formation of hepatic metastasis. Metastases formed in the liver of XN-treated mice revealed significantly larger areas of central necrosis and lower Ki67 expression scores compared to that of control mice. In conclusion, XN inhibits tumorigenicity of melanoma cells in vitro and significantly reduced hepatic metastasis of melanoma cells in mice. These data, in conjunction with an excellent safety profile that has been confirmed in previous studies, indicate XN as a promising novel agent for the treatment of hepatic (melanoma) metastasis.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Melanoma; Metastasis; Xanthohumol